Students' Learning Motivation in Online Learning System During Covid-19 Pandemic - Alani, Nabella; Wahyudin; Saud, Udin Syaefudin (International Conference on Elementary Education, 2022)
This research aims to describe the learning motivation of fourth grade students during online learning. The method of this research used is descriptive qualitative with research participants are 25 students of fourth grade and several representatives of parents to be interviewed. The research instrument used was a learning motivation questionnaire and also an interview instrument. The results showed that students' learning motivation during online learning was in the middle category with a score 2.96. The results of the interview also show that parents also play an important role in the level of student learning motivation.